Clinicopathological characteristics, evolution, and treatment outcomes of hormone receptor-negative/HER2-low metastatic breast cancer: a pooled analysis of individual patient data from three prospective clinical trials - Hu, Shihui; Zhao, Yannan; Xie, Yizhao; You, Shuhui; Hu, Xichun; Zhang, Jian; Wang, Leiping; Cao, Jun; Gong, Chengcheng; Wang, Biyun (Frontiers in Endocrinology, 2024)
Objective With the approval of trastuzumab deruxtecan for the treatment of unresectable/metastatic HER2-low breast cancer, human epidermal growth factor receptor 2 (HER2)-low has emerged as a clinically actionable biomarker. There is an urgent need for a deeper understanding of HER2-low breast cancer patients. Therefore, this study was conducted to explore the clinicopathological characteristics, the evolution of HER2-low status, and its impact on the prognosis of hormone receptor (HoR)-negative/HER2-low metastatic breast cancer (MBC) patients. Methods This pooled analysis included 350 metastatic triple-negative breast cancer (mTNBC) patients who received first-line platinum-based chemotherapy at Fudan University Shanghai Cancer Center from November 2007 to July 2022. Patients were categorized into HER2-0 and HER2-low groups based on their HER2 status. Baseline clinicopathological characteristics, evolution of HER2 status between primary and metastatic lesions, and treatment efficacy were compared between the two groups. Results Among the 350 mTNBC patients, 34.9% (122/350) were HER2-low and 65.1% (228/350) were HER2-0. Significant differences were observed between HER2-low and HER2-0 patients in terms of age and menopausal status. HER2-low patients were older (54 vs. 49 years, p=0.002) and had a lower proportion of premenopausal patients (32.8% vs. 52.6%, p<0.001) compared to HER2-0 patients. No significant differences were observed in progression-free survival (PFS) and overall survival (OS) between HER2-low and HER2-0 patients receiving first-line platinum-based chemotherapy (mPFS: 7.43 vs. 8.30 months, p=0.389, HR=1.11, 95% CI 0.88-1.40; mOS: 25.37 vs. 26.63 months, p=0.907, HR=1.02, 95% CI 0.76-1.37). Additionally, 32.3% (41/127) of patients exhibited discordant HER2 status between primary and metastatic lesions, primarily evolving from HER2-0 to HER2-low. Notably, patients with discordant HER2 status had significantly longer PFS compared to those with concordant status (mPFS: 11.07 vs. 7.53 months, p=0.020). The Cox multivariate analysis showed that HER2 status consistency (p=0.026) was an independent predictor of PFS. Conclusion In mTNBC patients, those with HER2-low status had similar responses to platinum-based chemotherapy as HER2-0 patients. There was significant discordance in HER2 status between primary and metastatic lesions. Patients with discordant HER2 status had better responses to platinum-based chemotherapy. Therefore, for patients with HER2-0 primary lesions, re-evaluation of HER2 status in metastatic lesions through biopsy may offer new treatment opportunities.